Identification of Potential Radiation Responsive Metabolic Biomarkers in Plasma of Rats Exposed to Different Doses of Cobalt-60 Gamma Rays - Hua Zhao; Cong Xi; Mei Tian; Xue Lu; Tian-Jing Cai; Shuang Li; Xue-Lei Tian; Ling Gao; Hai-Xiang Liu; Ke-Hui Liu; Qing-Jie Liu (SAGE Publishing, 2020)
Metabolomics has great potential to process accessible biofluids through high-throughput and quantitative analysis for radiation biomarker screening. This study focused on the potential radiation responsive metabolites in rat plasma and the dose-response relationships. In the discovery stage, 20 male Sprague-Dawley rats were exposed to 0, 1, 3 and 5 Gy of cobalt-60 gamma rays at a dose rate of 1 Gy/min. Plasma samples were collected at 72 h after exposure and analyzed using liquid chromatography mass spectrometry based on non-targeted metabolomics. In the verification stage, 50 additional rats were exposed to 0, 1, 2, 3, 5 and 8 Gy of gamma rays. The concentrations of candidate metabolites were then analyzed using targeted metabolomics methods. Fifteen candidate radiation responsive metabolites were identified as potential radiation metabolite biomarkers. Metabolic pathways, such as linoleic acid metabolism and glycerophospholipid metabolism pathways, were changed after irradiation. Six radiation responsive metabolites, including LysoPC(20:2), LysoPC(20:3), PC(18:0/22:5), L-palmitoylcarnitine, N-acetylornithine and butyrylcarnitine, had good dose-response relationships ( R 2 > 0.80). The area under the curve of the panel of the 6 radiation responsive metabolites was 0.923. The radiation exposure metabolomics biomarkers and dose-response curves may have potential for rapid dose assessment and triage in nuclear and radiation accidents.